Photoplethysmography-documented atrial fibrillation in the first week after catheter ablation is associated with lower success rates - Manninger, Martin; Hermans, Astrid N. L.; Caracioni, Andrei-Antonio; Rohrer, Ursula; Eberl, Anna-Sophie; Vernooy, Kevin; Zirlik, Andreas; Linz, Dominik; Scherr, Daniel (Frontiers in Cardiovascular Medicine, 2023)
Aims To test the feasibility of postprocedural photoplethysmography (PPG) rhythm telemonitoring during the first week after atrial fibrillation (AF) ablation and its predictive value for later AF recurrence. Methods PPG rhythm telemonitoring during the first week after the ablation procedure was offered to a total of 382 consecutive patients undergoing AF ablation. Patients were instructed to perform 1 min PPG recordings by a mobile health application 3 times per day and in case of symptoms. Clinicians assessed the PPG tracings via a secured cloud and the information was remotely integrated into the therapeutic pathway via teleconsultation (TeleCheck-AF approach). Results 119 patients (31%) agreed to perform PPG rhythm telemonitoring after ablation. Patients included in the TeleCheck-AF approach were younger compared to those who declined participation (58 ± 10 vs. 62 ± 10 years, p < 0.001). Median follow up duration was 544 (53–883) days. 27% of patients had PPG tracings suggestive of AF in the week following the ablation. In 24% of patients, the integration of PPG rhythm telemonitoring resulted in a remote clinical intervention during teleconsultation. During follow-up of one year, 33% of patients had ECG-documented AF recurrences. PPG recordings suggestive of AF in the week after ablation were predictive of late recurrences (p < 0.001). Conclusion PPG rhythm telemonitoring during the first week after AF ablation often triggered clinical interventions. Due to its high availability, PPG-based follow-up actively involving patients after AF ablation may close a diagnostic and prognostic gap in the blanking period and increase active patient-involvement.